Alexander von Humboldt: Wissenschaften zusammendenken (BOP Books, 2021)
Thinking the sciences together - this is a leitmotif of Alexander von Humboldt’s problem-oriented research. With this in mind, this volume brings together a series of contributions that deal with this research today from the perspective of various disciplines, in the sciences as well as in the humanities. The perspectives range from climate research, ecology, botany, zoology and volcanology to history, history of science, art history, cartography, literary studies and museology. Eleven essays discuss Humboldt’s contributions to the understanding of temperature changes, landscapes and species. They decipher his drawings, maps and infographics, they take us to the Berlin of his youth, on the trail of migrating plants and to the summits of Andean volcanoes.